Effects of Real-time EMS Direction on Optimizing EMS Turnaround and Load-balancing Between Neighboring Hospital Campuses. (2nd November 2019) - Felice, Joseph; Coughlin, Ryan F.; Burns, Kevin; Chmura, Christopher; Bogucki, Sandy; Cone, David C.; Joseph, Daniel; Parwani, Vivek; Li, Fangyong; Saxa, Thomas; Ulrich, Andrew
Abstract: Background: Implemented in September 2017, the "nurse navigator program" identified the preferred emergency department (ED) destination within a single healthcare system using real-time assessment of hospital and ED capacity and crowding metrics. Objective: The primary objective of the navigator program was to improve load-balancing between two closely situated emergency departments, both of which feed into the same inpatient facilities of a single healthcare system. A registered nurse in the hospital command center made real-time recommendations to emergency medical services (EMS) providers via radio, identifying the preferred destination for each transported patient based on such factors as chief complaint, ED volume, and waiting room census. The destination decision was made via the utilization of various real-time measures of health system capacity in conjunction with existing protocols dictating campus-specific clinical service availability. The objective of this study was to evaluate the efficacy of this real-time ambulance destination direction program as reflected in changes to emergency medical services (EMS) turnaround time and the incidence of intercampus transports. Methods: A before-and-after time series was performed to determine if program implementation resulted in a change in EMS turnaround time or incidence of intercampus transfers. Results: Implementation of the nurse navigator program was associated with a statistically significant decrease in EMS turnaround times for all levels of dispatch and transport at both hospital campuses. Intercampus transfers also showed significant improvement following implementation of the intervention, although this effect lagged behind implementation by several months. Conclusion: A proactive approach to EMS destination control using a nurse navigator with access to real-time hospital and ED capacity metrics appears to be an effective method of decreasing EMS turnaround time.